Seismic evaluation and studying the effect of friction damper - Miri, Mahmood; Kahkeshan, Aidin (International Journal of Engineering and Technology, 2014)
Water elevated tanks are one of the most important tools in supplying water for cities. Due to their damages in previous earthquakes, and the necessity for keeping them in safe and usable condition after earthquakes is obvious. Thus, by making various modeling, their behavior under seismic loading is investigated. Moreover, the pros and cons of dampers are also evaluated. In this thesis, the proposed concrete water tank is modeled under three different earthquakes of Tabas, Northridge and Chichi. Moreover, the damper is located in three various positions. The results are illustrated for different fullness of tanks.   Keywords: Seismic Evaluation, Friction Damper, Earthquake.